Pengaruh Sistem Pengendalian Internal Pemerintah, Whistleblowing System, Dan Kompetensi Sumber Daya Manusia Terhadap Pencegahan Fraud (Studi Pada Inspektorat Daerah Kota Bandung) - Lathifah Nur'aini; Salza Adzri Arismutia (Komunitas Dosen Indonesia, 2024)
The goal of this study is to determine the relationship between fraud prevention in the Bandung City Regional Inspectorate and the government's internal control system, whistleblower system, and human resource competency. This data collection used several studies, namely, field research, literature study, interviews, and distributing questionnaires to 65 respondents with a research sample of Bandung City Regional Inspectorate Auditors which was the method used to collect data. Quantitative techniques, such as verification and descriptive methods, were employed in this study. In this study, saturated sampling combined with non-probability sampling was the research sample strategy or sampling technique. The degree of sample influence is measured using the coefficient of determination, multiple linear regression analysis, classical assumption test analysis, and hypothesis testing. The Statistical Product and Service Solution Application version 26 is used in this data processing. Thus, the study's findings suggest that while human resource competency has no discernible impact on fraud prevention, the government's internal control and whistleblower systems have an impact on it. Simultaneous research findings indicate that fraud prevention is influenced by the government's internal control system, whistleblower mechanism, and human resource competency. Therefore, it can be said that internal government controls account for 74% of fraud prevention, external variables account for 26%, and the violation reporting system and human resource competency account for 74%.